2020
DOI: 10.1017/jfm.2020.199
|View full text |Cite
|
Sign up to set email alerts
|

Interface-resolved simulations of small inertial particles in turbulent channel flow – CORRIGENDUM

Abstract: Equation (2.10) in Costa, Brandt & Picano (2020) for the lift force model used in the point-particle direct numerical simulations (DNS), and which is derived from the classical lift force of Saffman (1965),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 4 publications
3
17
0
Order By: Relevance
“…These studies mostly focused on inertial particles with a size much larger than Kolmogorov length scale, and detailed mechanisms of turbulence modulation were concluded using various statistical methods. Recently, by comparing the results between particle-resolved simulation and one-way coupled point-particle simulation, Costa et al (2020aCosta et al ( , 2020b found that when the modified Saffman lift force is included, the statistical results between two simulations are very similar, thus supporting the validity of the pointparticle method.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…These studies mostly focused on inertial particles with a size much larger than Kolmogorov length scale, and detailed mechanisms of turbulence modulation were concluded using various statistical methods. Recently, by comparing the results between particle-resolved simulation and one-way coupled point-particle simulation, Costa et al (2020aCosta et al ( , 2020b found that when the modified Saffman lift force is included, the statistical results between two simulations are very similar, thus supporting the validity of the pointparticle method.…”
Section: Introductionmentioning
confidence: 94%
“…( 2), the terms on the right hand side are drag force, buoyancy force, lift force, pressure gradient force, and added mass force, respectively. Their contributions to the total force when compared with the drag force are discussed in Armenio and Fiorotto (2001) and Mortimer et al (2019).T h el i f tf o r c e [ Costa et al, (2020a[ Costa et al, ( ,2020b], the pressure gradient force, and the added mass force (Mortimer et al,2 0 1 9 ) are included because of their gradually increasing effect upon approaching the wall. Costa et al (2020aCosta et al ( , 2020b also found that the point-particle method with the Saffman lift model included can have similar statistical results with those from the particle-resolved method.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Among the catalogue of expressions for shear-induced lift force, Saffman-Mei was chosen as its ability to capture near-wall statistics is corroborated by state-of-the-art particle-resolved DNS (Costa, Brandt & Picano 2020b). As such, equations for particle motion are (ODEs) associated with particle motion are integrated in time through an implicit Euler scheme.…”
Section: Computational Set-upmentioning
confidence: 99%
“…Liu & Agarwal 1974) and the analytical work presented in § 1.1. Sets 3 and 4, are similar to Sets 1 and 2, respectively, except that the Saffman-Mei lift force F l is included in the particle dynamics, which was found to yield better agreement with fully resolved particle simulations (Costa et al 2020b). The purpose of these four sets is to test the robustness of particle-wall interaction and force treatments on particle dynamics.…”
Section: Computational Set-upmentioning
confidence: 99%